2007
DOI: 10.1017/s0265021506001876
|View full text |Cite
|
Sign up to set email alerts
|

Study on the usefulness of precise and simple dynamic balance tests for the evaluation of recovery from intravenous sedation with midazolam and propofol

Abstract: The timed 'up & go' and maximum-speed walking tests are useful simple dynamic balance tests well correlated with precise computerized dynamic posturography for the evaluation of the recovery of dynamic balance from midazolam sedation in younger adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…We previously demonstrated that this is also true when maintaining sedation impaired balance [8] and sleep-deprived balance [12]. The results in the current study are in agreement with previous findings that propofol impairs postural steadiness, but less so than midazolam [3,4].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…We previously demonstrated that this is also true when maintaining sedation impaired balance [8] and sleep-deprived balance [12]. The results in the current study are in agreement with previous findings that propofol impairs postural steadiness, but less so than midazolam [3,4].…”
Section: Resultssupporting
confidence: 93%
“…Fujisawa demonstrated that computerized dynamic posturography was affected by midazolam [1], that these effects persisted longer in the elderly than in young people [2], and that the effects were less persistent with propofol sedation [3]. These authors further demonstrated that the results of the timed up and go test, in which a patient stood up, walked five meters, turned, and returned to their chair, correlated with the computerized dynamic posturography score [3,4]. Although computerized dynamic posturography and the timed up and go test may be sensitive measures of recovery, these tests may not be appropriate for all patients.…”
Section: Introductionmentioning
confidence: 99%
“…Fujisawa et al. reported that 0.07 mg.kg −1 midazolam reduced grip strength more than propofol at predicted effect‐site concentration of 2.2 μg.ml −1 . Because benzodiazepines such as midazolam produce centrally acting muscle relaxation via α 2 ‐GABA A receptors , it has been suggested that this reduction in grip strength negates the increase in grip strength induced by propofol.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, dentists sometimes suffer from control behavioural management of patients. There have been a number of detailed studies on central nervous system (CNS) effects, circulatory and respiratory effects, and wakening with intravenous sedation by midazolam or propofol [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , however, only few studies assessing physical movement or muscle power during sedation [19] , [20] .…”
Section: Introductionmentioning
confidence: 99%